Silicon-germanium Single-heterojunction Bipolar Transistor - Khanduri, G.M.; Panwar, B.S. (Defence Science Journal, 2006)
The cutoff frequency performance of an NPN Si/SiGe/SiGe single-heterojunction bipolar transistor (SiGe SHBT) at high collector current densities has been analysed using a 2-D MEDICI device simulator. A conventional NPN Si/SiGe/Si double-heterojunction bipolar transistor (SiGe DHBT) having uniform 20 atomic per cent of germanium in the base region has been investigated for comparison. The analysis shows the formation of a retarding potential barrier for minority carrier electrons at the base-collector heterojunction of the DHBT structure. Whereas, the base-collector homojunction of the SiGe SHBT structure, having a uniform 15 atomic per cent of germanium profile in its base and collector, inhibits the formation of such a retarding potential barrier, the SHBT structure with a base-collector homojunction shows an improved cutoff frequency at high collector current density in comparison with conventional SiGe DHBT, which makes it more promising for high speed, scaled down, field-specific applications.